Development of Pokkali Rice-Based Fruit Blended Probiotic Drink and Evaluation of Its Sensory Parameters and Nutritional Content - P.S, Soumya; Valappil, Asna Noushad Changarath; Varghese, Varsha Clara (Asian Journal of Biological and Life Sciences, 2024)
Background: The World Health Organization (WHO) defines probiotics as live microorganisms that, when consumed in adequate amounts, offer health benefits to the host Probiotics can be derived from dairy-based sources like bovine milk or non-dairy sources like fruits, vegetables, cereals and legumes. They offer various benefits such as reducing cholesterol levels, boosting the immune system and improving lactose metabolism, protein digestibility and vitamin and mineral synthesis. Aim: The probiotic foods are mostly found in milk-based products on the market worldwide, with very few attempts being undertaken to create probiotic foods utilising other fermentation substrates, like cereals, pulses and vegetables. The focus has shifted to their utilisation as raw materials for the creation of new fermented functional products due to their wide availability and significant nutritional value. In the present study, addition of pokkali rice with different fruit pulp in variant concentrations to enhance the flavor with the intention of consumers’ acceptance. Pokkali rice has distinct taste and high protein content and it possesses several medicinal properties. Materials and Methods: Pokkali rice and fresh and ripened fruits such as Mango, Papaya, Strawberry, Guava and Aloe vera were collected from the farmers from Ezhikara and local market in Ernakulam. Pure cultures of the probiotic strain (Lactobacillus helveticus) were purchased from KVASU College of Dairy Science and technology, Mannuthy, Thrissur. Results: Five products and three treatments (along with one control) were standardized, each with three replications. The yogurts were evaluated for taste and quality parameters using a 9-point hedonic scale by a panel of 10 judges. The best sample was chosen based on Kendall’s coefficient of concordance. The Pokkali rice-based probiotic drink T3 was the most preferred among the treatments. The proximate value was highest in the Pokkali rice-based papaya blended probiotic drink. Conclusion: The greatest form of milk for hypoallergenics is thought to be rice milk. If you have soy or cow milk allergy, it is best to drink rice milk. Since rice milk has unsaturated fat and no cholesterol, it is suggested for people who are lactose intolerant. The results of the current study confirm that adding fruit pulp to the Pokkali rice-based probiotic drink significantly enhanced its sensory appeal and nutritional properties.
Keywords: Fermented products; Lactobacillus helveticus; Pokkali rice; Probiotic drink